Healthy Obese and Post Bariatric Patients – Metabolic and Vascular Patterns - Bachmayer, C.; Lammert, A.; Hasenberg, T.; Hammes, H.-P. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Obesity and the metabolic syndrome (MetS) are associated with endothelial dysfunction (ED). An established method to determine ED is retinal vessel analysis. Obesity is associated with MetS, but obese patients not matching all criteria of the MetS and therefore defined as metabolically healthy obese subjects (MHOS) exist. Bariatric surgery may be an appropriate option to treat morbid obesity. The aim of this study was to compare MetS, MHOS and post bariatric patients in adipocytokine patterns and ED.Arterio-venous ratio (AVR) and vessel diameters from retinal photographs (IMEDOS™), parameters of MetS (IDF) and obesity-associated factors (hsCRP, TNF, Il-6, MCP-1, sICAM, sVCAM, IGF-BP3, RBP 4 and adiponectin) were assessed in 51 obese patients with MetS, 20 obese patients without MetS and 21 patients pre and post bariatric surgery.Bariatric surgery improved ED as reflected by AVR and venous diameters (p<0.05 for both). These improvements were associated with lower levels of fasting plasma glucose, insulin, HOMA-IR, LDL-C, triglycerides, cholesterol, hsCRP, sICAM, and higher levels of adiponectin and RBP4 (p<0.05 for each parameter). MHOS differed from MetS by neck circumference, fasting plasma glucose, HOMA-IR, triglycerides, HDL-C, sICAM, and adiponectin (p<0.05), but not by RRs, RRd, insulin, LDL-C, hsCRP, Il-6, TNF, MCP-1, sVCAM, RBP-4, IGF-BP3, and retinal ED.These data indicate that improved insulin-sensitivity and reduced inflammatory mediators characterize the metabolic outcome of postbariatric patients in comparison to MHOS. Thus, MHOS characterizes an intermediate state between MetS and postbariatric patients.
Keywords: adipocytokines; bariatric surgery; endothelial dysfunction; healthy obesity; metabolic syndrome